Addition of purwoceng extract (Pimpinella alpina Molk) to feed to improve the reproductive performance of Barbonymus schwanenfeldii - Syawaliah, Nurfazriyanti; Farastuti, Eko Rini; Wahyudin, Yudi; Lesmana, Dudi (JURNAL MINA SAINS, 2025)
Although Tengadak fish farming is not yet popular and its quantity and productivity are relatively low, it has the potential to be developed in Indonesia. The biggest challenge is the long spawning stage, so reproductive manipulation with synthetic hormones is necessary. This study aims to determine the optimal dose of purwoceng extract (Pimpinella alpina Molk.) in feed to improve the reproductive performance of barbel fish (Barbonymus schwanenfeldii). This research project was conducted at the Aquatic Laboratory of the Faculty of Agriculture at Djuanda University in Bogor from November 2023 to February 2024. A completely randomized design (CRD) with four treatments and three replicates was used, and the data were analyzed using ANOVA. The treatments included: P1 (control, no purwoceng extract); P2 (5 g purwoceng extract per kg of feed); P3 (10 g purwoceng extract per kg of feed); and P4 (15 g purwoceng extract per kg of feed). Four female tengadak fish with an average weight of 156 g and a length of 21 cm were used for each treatment. Results showed that administering purwoceng extract at a dose of 15 g/kg of feed resulted in an absolute weight growth of 18.23 ± 0.33 grams and the highest fecundity of 36,005 eggs. There was no significant difference in absolute length growth among the treatments. Proximate analysis of the gonads revealed an average protein content of 10.78%, fat content of 23.8%, moisture content of 75.6%, and ash content of 1.4%. Based on the research results, purwoceng extract can improve the reproductive performance of tengadak fish.